Review of Common Superstition-based Therapies in Qajar Era, Iran - Hamed Monfared, Aidin; Emadi, Abd-al Rasoul (Advances in Nursing & Midwifery, 2018)
In Arabic, every strange word that arose from a world other than human world, human science and experience is called superstition. (Seyyed ibn Tavous, p. 260) Some superstitious beliefs are specific to a community or a particular culture and some of these beliefs are specific to a particular gender or even a particular person. In Iran from ancient times to the Qajar era, especially before the Daroulfonon institute and a gradual transition from traditional to modern medicine, the role of superstition in the field of healthcare was applicable. Due to lack of educated physicians in community, lack of health care facilities and low-level health care system many of common people were resorting to magic and extravagant and non-scientific styles to cure illnesses. Methodology: This research is based on the fact that the target community of study is Iran's Qajar era, and practical field study is not possible; hence, it has fully utilized the library research method and attempted to use first hand resources from that era. This study aims to investigate the superstitions prevailing in the community for treatment of diseases in the Qajar period, to provide an underlying study for the new era researcher’s studying superstition therapy in present-day society, so there can be a comprehensive comparison between superstition in Present day and Qajar era.